Analisis Pengaruh Kredit terhadap Efisiensi Usahatani Padi di Pulau Jawa: Badan Pusat Statistik, Institut Pertanian Bogor - Darwis Abubakar; lukytawati Anggraeni; Anna Fariyanti (IPB University, 2019)
Efforts to increase rice productivity through extensification are increasingly difficult, so production efficiency becomes an important alternative. This paper aims to estimate the determinants of production factors and level of efficiency of rice farmers and the impact of access to credit, credit of formal and semiformal financial institutions on technical inefficiencies of rice farmers. Cross section data from 9,127 farmers in Java was obtained from the Survey (Rumah Tangga Usaha Tanaman Padi 2014). Analytical method used is stochastic frontier production function to analyze production and technical efficiency, dual frontier cost function to estimate allocative and economic efficiency and technical inefficiency function to reveal the effect of credit. The result is farmers on Java island have been technically efficient but not allocatively and economically efficient yet. Farmers who receive credit, credit from formal financial institutions and semiformal institutions are more efficient than non-credit farmers.